SEVERE BACTERIAL AND OPPORTUNISTIC INFESTIONS IN ENDOGENOUS CUSHING'S SYNDROME: A CASE SERIES - SB, Samsuddin; A, Nasruddin; NM, Noor; MB, Mohamad (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Cushing’s syndrome is a clinical condition characterised by elevated serum cortisol levels from either exogenous or endogenous glucocorticoids. Hypercortisolemia impairs immune function and increases host susceptibility to bacterial, viral and fungal infections. We report two cases of endogenous Cushing’s that succumbed to severe bacterial and opportunistic infections. CASE 1 : A 69-year-old lady with diabetes and hypertension presented with lower limb weakness, easy bruising and severe hypokalemic alkalosis. Biochemical investigations confirmed Cushing's as demonstrated by elevated 24- hour urine cortisol and non-suppressible cortisol after overnight and low dose dexamethasone suppression test. Adrenocorticotropic hormone (ACTH) was suppressed while dehydroepiandrosterone sulfate (DHEAS) and androstenedione were elevated. Magnetic resonance imaging of the abdomen revealed an adrenocortical carcinoma with liver and lung metastases. She required high doses of insulin, potassium and ketoconazole to control her disease. She developed severe Klebsiella pneumonia with aspergillosis and finally expired. CASE 2 : A 59-year-old lady was diagnosed with ACTH-dependent Cushing’s syndrome when she presented with weight gain, hirsutism and persistent hypokalemia. Initial workup revealed a mediastinal mass which was reported as a neuroendocrine tumour by biopsy. Biochemical investigations were consistent with Cushing’s, with elevated serum ACTH. She was given ketoconazole and metyrapone and was subsequently admitted for hospital-acquired and opportunistic fungal pneumonia. She underwent removal of the mediastinal tumour. Post-surgery, her disease was still active with a residual tumour. Ketoconazole was restarted but she succumbed to Salmonella sepsis despite aggressive treatment. CONCLUSION Patient’s with Cushing's syndrome are susceptible to severe and life-threatening infections. The diagnosis of infections is often made late because the signs and symptoms are often masked by hypercortisolemia. Treatment with anticortisol drugs often unmasks infections. Hence, there is a need for a high index of suspicion in order to diagnose opportunistic infections early.